Axial Compressive Behavior of Lithium Slag Recycled Coarse Aggregate Concrete-Filled Circular Steel Stub Columns - Qiao-Huan Wang; Jiong-Feng Liang; Chun-Feng He; Wei Li (Advances in Materials Science and Engineering)
In order to study the axial compression performance of lithium slag recycled concrete short columns in circular steel tubes, eight short columns were designed and tested. The main influence parameters of the specimens are lithium slag replacement rate and recycled concrete replacement rate. The test process and failure mode of the specimens are observed, and the load-displacement curve is drawn. The influence of the replacement rate on the axial compression performance of the specimens is analyzed. The results show that recycled concrete replacing natural coarse aggregate will reduce the mechanical properties of specimens, but lithium slag mixed into recycled concrete can compensate for the lack of mechanical properties of recycled concrete, and the specimens mixed with lithium slag and recycled concrete have good stiffness and ductility.